ChemInform Abstract: A New Oxytelluride: Perovskite and CsCl Intergrowth in Ba3Yb2O5Te. Issue 34 (1st August 2013) - Whalen, J. B.; et al., et al.
Abstract Single crystals of the title compound are obtained from a Ba flux containing Te and yttria (molar ratio 20:1:2; stainless steel crucible in evacuated quartz ampoule, 1000 °C, 20 h; slow cooling to 600 °C and separation of the crystals from the flux by centrifugation).